Determinants of bank M&As in Central and Eastern Europe - Alin Marius Andrieş; Sabina Cazan; Nicu Sprincean (Journal of Risk and Financial Management, 2021)
This paper analyzes the determinants of bank mergers and acquisitions (M&As) from a bank-level perspective. The main objective of the study is to identify those mutual characteristics of all banking institutions from Central and Eastern Europe that are prone to be acquired versus acquirer, or national versus cross-border. Using a database of more than 200 M&As transactions between 2000 and 2018 within Central and Eastern Europe, we document the main characteristics that influence the decision of merging, including the size of the bank, profitability, lending activities, liquidity, bank concentration, banking system stability, government effectiveness, regulatory quality, and the level of inflation. Higher effective average tax rate, which is associated with reduced tax avoidance, influences banks in a positive manner to be involved in the M&A process, findings that hold for targeted banks and domestic transactions. Furthermore, the analysis highlights the changes the financial crisis has projected on investors' behavior.
Keywords: 330; bank; mergers and acquisition; financial crisis